Effect of magnetic field on spoke behaviour in HiPIMS plasma. (12th February 2018) - Hnilica, J; Klein, P; Šlapanská, M; Fekete, M; Vašina, P
Abstract: The objective of this paper is to study the effect of magnetic field strength on spoke behaviour in a high power impulse magnetron sputtering discharge. In three magnetic field configurations, a broad range of experimental conditions was investigated by high-speed camera imaging. The dual image feature of the employed camera enabled us to determine the shape and spoke mode number, as well as the velocity of the spokes. Five distinct spoke shapes were detected. For each magnetic field, a map was created relating the occurrence of the spoke shape with the discharge conditions. Similarly, the spoke mode number, as well as the spoke velocity, was found to be strongly dependent on the discharge conditions. Based on the optical emission results, it was proposed that the trailing edge of the triangular spoke is related to the production of secondary electrons created by argon ions on the spoke edges, while in the case of a round spoke shape, the secondary electrons are mainly created by multiple charged titanium ions in the centre of the spoke.